2017
DOI: 10.1002/cdq.12110
|View full text |Cite
|
Sign up to set email alerts
|

“Yes, I Can”: Testing an Intervention to Increase Middle School Students’ College and Career Self‐Efficacy

Abstract: Middle school is the appropriate time for students to begin exploring careers and improving self-efficacy; however, empirically supported career and college readiness interventions for U.S. middle school students are limited. Examining the effect of an intervention that combined a virtual experience and a local college visit on middle school students (99 girls, 74 boys), the authors found that participating students had higher levels of college and career self-efficacy than did nonparticipating students. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 29 publications
(40 reference statements)
0
20
1
1
Order By: Relevance
“…Hambatanhambatan yang ada dalam mengambil keputusan untuk melanjutkan studi seperti kondisi sosial ekonomi keluarga, dukungan orangtua, ketatnya persaingan memasuki perguruan tinggi, pengaruh teman sebaya, dan lain sebagainya akan ditanggapi secara berbeda pada siswa; dan sangat bergantung pada kondisi self-efficacy yang dimiliki oleh masing-masing siswa. Jika siswa memiliki self-efficacy yang tinggi, maka siswa akan menganggap bahwa hambatanhambatan tersebut bukanlah hambatan yang berarti (Glessner, Rockinson-Szapkiw, & Lopez, 2017). Namun, jika siswa memiliki self-efficacy yang rendah, maka siswa cenderung menganggap hambatan-hambatan tersebut adalah hambatan yang tidak mungkin dapat ia tangani atau hadapi (Snyder et al, 2002).…”
Section: Pembahasanunclassified
“…Hambatanhambatan yang ada dalam mengambil keputusan untuk melanjutkan studi seperti kondisi sosial ekonomi keluarga, dukungan orangtua, ketatnya persaingan memasuki perguruan tinggi, pengaruh teman sebaya, dan lain sebagainya akan ditanggapi secara berbeda pada siswa; dan sangat bergantung pada kondisi self-efficacy yang dimiliki oleh masing-masing siswa. Jika siswa memiliki self-efficacy yang tinggi, maka siswa akan menganggap bahwa hambatanhambatan tersebut bukanlah hambatan yang berarti (Glessner, Rockinson-Szapkiw, & Lopez, 2017). Namun, jika siswa memiliki self-efficacy yang rendah, maka siswa cenderung menganggap hambatan-hambatan tersebut adalah hambatan yang tidak mungkin dapat ia tangani atau hadapi (Snyder et al, 2002).…”
Section: Pembahasanunclassified
“…Novel research has indicated that school provides an appropriate setting for students to explore and improve career efficacy (Glessner, Rockinson-Szapkiw, & Lopez, 2017). Career management is a core concept among students as they expect to be employed and be required to perform with regard to their personal interests and personalities.…”
Section: Overview Of Career Counseling In Schoolsmentioning
confidence: 99%
“…A viewpoint held by Maxey and Kezar (2016) indicate that a detailed planning regarding career selection could aid the students in choosing respective study programs that are aligned to individual vocation. Glessner et al (2017) contend that recent trends in high education depict the necessity to customize programs to align with the labor market. Further, learners need to start career planning before they undertake various degrees so that they establish compatibility with regards to the types of employment desired (Palade & Constantin, 2012).…”
Section: Overview Of Career Counseling In Schoolsmentioning
confidence: 99%
“…Intervention study results have indicated that targeted career interventions for middle and early high school aged students significantly increases career self-efficacy (Alverez, 2009;Glessner, Rockinson-Szapkiw, & Lopez, 2017). Qualitative studies of gifted individuals showed that supportive external influences can significantly shape career selfefficacy (Hau, 2002;Penny, 2013).…”
Section: Stem Excellence and Leadership Programmentioning
confidence: 99%
“…Similarly, another intervention study examined the effects of a career educational program and college visit on students' college and career self-efficacy (Glessner, Rockinson-Szapkiw, & Lopez, 2017). In this study, 173 eighth-grade students -105 in the treatment group and 68 in the control groupreported self-reported college and career self-efficacy scores.…”
Section: Stem Excellence and Leadership Programmentioning
confidence: 99%